In Vitro and In Vivo wound healing studies of standardized extract of Centella asiatica - Abdul Aziz, Huwaida; Bakhtiar, Muhammad Taher; Sh Ahmed, Afnan; Wan Sulaiman, Wan Mohd. Azizi; Darnis, Deny Susanti; Roy Chowdhury, Shiplu; Ahmad, Farediah; Zakaria, Zainul Amiruddin (2016)
The current study evaluates the wound healing efficacy of Centella asiatica via in vitro scratch assay and in vivo circular wound excision model. The ethanol extract was qualitatively identified using thin layer chromatography and the positive fraction containing asiaticoside was further quantified using reverse-phase HPLC. The asiaticoside rich fraction was subjected to: i) colorimetric MTT (methylthiazoltetrazolium) cell viability study following incubation with human dermal fibroblast (HDF) and human dermal keratinocyte (HaCaT); ii) in vitro 12-well plate scratch assay (using HDF and HaCaT cells); iii) topical application (40, 10, and 2.5%, w/w) on in vivo circular wound excision of rabbits. Data on wound contraction, epithelization period, hydroxyproline content and histophatological analysis was collected from in vivo study. The result showed that the methanol fraction of extract contained about 2.4% of asiaticoside. Based on the results of colorimetric MTT (methylthiazoltetrazolium) cell viability assay, both HDF and HaCaT showed significant stimulation upon application of the methanolic fraction of extract at concentrations of 100 µg/mL and 0.19 µg/mL. In the scratch assay, methanol fraction of extract with concentration of 0.2 µg/mL and 100 µg/mL showed significant effect on HDF and HaCaT compared to the positive control (P< 0.05). In vivo, it was shown that the methanol fraction of the standardized extract induced collagen synthesis. Histopathology data also concluded that dose-dependent effect of the tested extract as a wound healing was present. In conclusion, the claim on the presence of wound healing properties in C. asiatica had been well supported based on the results obtained in this study.